2001
DOI: 10.1007/s001980170023
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Proximal Femur Osteoporosis in Men Aged 50 Years or Older

Abstract: The objective of this study was to analyze the risk factors for osteoporosis in 325 volunteer men aged 50 years or older. Participants completed questionnaires including demographic and social information, personal medical history, maternal and paternal history of bone fracture after the age of 50 years, smoking habit, alcoholic beverage consumption, calcium intake and present and past physical activities. The individuals were submitted to bone densitometry of the femoral neck and to anthropometric measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 34 publications
2
27
0
6
Order By: Relevance
“…However, they may also inhibit the production of cytokines that mediate osteolysis. Both present and past smoking habits have been found to be risk factors for proximal femoral osteoporosis [21,25], and it is known that active bone remodelling and localised osteoporosis occur after prosthetic implantation in this region [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, they may also inhibit the production of cytokines that mediate osteolysis. Both present and past smoking habits have been found to be risk factors for proximal femoral osteoporosis [21,25], and it is known that active bone remodelling and localised osteoporosis occur after prosthetic implantation in this region [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have suggested that higher calcium intake is associated with lower rates of bone loss [19][20][21], several studies, including ours, failed to establish an association between lower calcium intake and osteoporosis [22,23]. Therefore, we believe that further studies that stringently assess calcium intake are necessary.…”
Section: Discussionmentioning
confidence: 66%
“…Other risk factors were low BMI, physical inactivity (in the last 12 months), smoking, lack of routine use of thiazide, white ethnicity, and maternal history of osteoporosis after 50 years. 12 In a recently published study, which excluded men receiving antiandrogenic therapy, we demonstrated that low BMI and decline of sex steroids explain much of the association between aging, increased bone turnover and osteoporosis. 13 The relationship between body composition and BMD was previously described by Zerbini et al 14 The senile osteoporosis tends to be multifactorial, related to age, inactivity, hypogonadism, low intake and/or calcium absorption and hyperparathyroidism secondary to vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 72%